The linkage between population growth, GDP and food security in Oman: vector error correction model analysis - Devesh, Sonal; Abdullah, M. Asrul Affendi (Journal of Scientific & Technology Research, 2020)
The paper examines the determinants of food security in Oman during the period 1980-2017. It investigates the influence of population growth rate and GDP per capita on food import bill. Cointegration and vector error correction model (VECM) approach have been used to identify the long term and short-term relationship of food security determinants. The finding indicates that food security in Oman is positively influenced by the population growth rate and GDP/capita. The error correction term suggests that 98 percent of the total disequilibrium in food security was being adjusted every year which a fast adjustment is justifiable for an oil producing country.